THE EFFECT OF ECONOMIC GROWTH, INFLATION AND BUSINESS CONFIDENCE INDEX ON UNEMPLOYMENT IN ASEAN-5 - Yusri, Kamilatun Ahsana; Nikensari, Sri Indah; Iranto, Dicky (Faculty of Economics and Business, Universitas Negeri Jakarta, 2021)
This study aims to see the effect of of economics growth, inflation, and business confidence indexin ASEAN-5. The method used in this research is panel data regression method with VectorError Correction model. This research was conducted in 5 countrys in ASEAN for fiveteenyears, 2005-2019. The variables in this study consisted of the economics growth represented bypercentage of GDP (X1), inflation represented by consumer price index (X2), business confidenceindex represented by percentage of business confidence index (X3), and unemploymentrepresented by percentage of unempolyment rate (Y). This data is secondary data obtainedthrough World Bank and Trading Economics in ASEAN-5. The results of this study prove thatthe variable of economics growth in 1st lag isn’t significant on unemployment, but in 2nd and3rd lag are significant on unemployment. While the variables of inflation and businessconfidence index are significant on unemployment.